1 ) - 30 + 6 . (-1) = A ( ) - 36 B ( ) + 24 C ( ) – 24 D ( ) + 40 2 ) – 4 . (- 5) – + (- 3) = A ( ) + 8 B ( ) + 388 C ( ) + 16 D ( ) – 32 3 ) = A ( ) B ( ) C ( ) -3 D ( ) 4 ) = A ( ) B ( ) C ( ) D ( ) - 1 5) = A ( ) B ( ) +2 C ( ) + 6 D ( )
Soluções para a tarefa
Respondido por
0
Resposta:
sim
Explicação passo-a-passo:
de ACORDO
Perguntas interessantes
Administração,
9 meses atrás
História,
9 meses atrás
Português,
1 ano atrás
História,
1 ano atrás
Ed. Física,
1 ano atrás
Sociologia,
1 ano atrás
Português,
1 ano atrás